PERKEMBANGAN GLOBAL PEMERINTAHAN BERBASIS ELEKTRONIK: ANALISIS BIBLIOMETRIK - Wulandari, Serly; Abdilah, Isna Muhsin; Samsudin, Samsudin; Jumino, Tri Kisowo; Ruhana, Faria (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
The advancement of Information and Communication Technology (ICT) has brought significant changes in the way humans interact in society, including in the governance process. Where the government continues to strive to improve the quality of public services through system automation and encourage innovation to create more efficient and effective services known as e-government or digital government. This study aims to analyze issues related to the global development of electronic-based government using literature studies from the Scopus database, and describe the findings on 1) the development of publication trends, 2) the most influential researchers and articles, 3) the map of interrelationships between authors viewed from the author's country of affiliation 4) the map of article linkages viewed from the co-occurrence of the author's keywords. The researcher used bibliometric analysis processed with the Vosviewer application. The results of the analysis show that the topic has begun to receive research attention since 1992 with the highest number of publications occurring in 2013 as many as 20 articles. The article entitled Trust and electronic government success: An empirical study written by Teo T.S.H.; Srivastava S.C.; Jiang L in 2008 received the highest number of citations of 1095 citations. The analysis of articles seen from the author with the highest order comes from the United States, with the most publications, namely 54 articles and 10 total networks. Then when viewed from the map of the co-occurrence relationship of the author's keywords, 4 (four) clusters are formed. Problems related to information are the only topics that are most often discussed, with e-government systems and electronic government adoption as topics that have been widely studied since 2018. Potential topics that can be further studied in the future are accessibility, author, hypothesis, service quality, acceptance, electronic government service, practical implications, questions, increases, abilities and egov.